Pengembangan Potensi Wisata Berbasis Pariwisata Pedesaan di Desa Adat Bugbug Kabupaten Karangasem Bali - Ni Made Sri Puspa Dewi Roels; Nisa Rahmaniyah Utami (Media Wisata, 2021)
Bugbug Traditional Village located in East Bali. Bugbug Traditional has a lot of excellent tourism potential to be developed into rural tourism. This research is expected to support the role of tourism managers in the Bugbug Traditional Village to be able to run optimally in managing all tourism potential. Research data was collected through observation, interviews, literature study, Focus Group Discussion, and documentation. Data analysis uses analysis data qualitative methods, namely data collection, data reduction, data presentation, and concluding. This research results in the development of tourism in the Bugbug Traditional Village into rural tourism, which consists of nature tourism and cultural tourism. Nature tourism is carried out with agricultural education activities and tour the village—cultural tourism in witnessing local cultural wisdom, like traditional ceremonies and local traditions. In addition, the results of this study compiled several programs to optimize the role of the Bugbug Traditional Village Tourism Management Agency. The programs include: approaching and providing assistance to the institutions, forming an organizational structure and collaborative management.